Young Women Learning in Social Struggle - Rachel Gouin (Adult Education Research Conference, 2007)
Based on a study conducted with young activists, this paper discusses social movement learning and the personal and social transformations it fosters. The author presents a framework that broadens conventional interpretations of political economy by adding patriarchy and white supremacy to capitalism, as systems of domination, and as points of analysis.